2018
DOI: 10.1523/jneurosci.1350-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H1 Receptor Contributes to Vestibular Compensation

Abstract: Vestibular compensation is responsible for the spontaneous recovery of postural, locomotor, and oculomotor dysfunctions in patients with peripheral vestibular lesion or posterior circulation stroke. Mechanism investigation of vestibular compensation is of great importance in both facilitating recovery of vestibular function and understanding the postlesion functional plasticity in the adult CNS. Here, we report that postsynaptic histamine H1 receptor contributes greatly to facilitating vestibular compensation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 73 publications
0
42
0
3
Order By: Relevance
“…Nonetheless, these agents have associated side effects, with sedation being a common drawback of antihistamines, and in many cases, their efficacy in reducing vertigo is questionable (Strupp, Zwergal, Feil, Bremova, & Brandt, 2015). Recent preclinical data furthermore suggest that H 1 receptor antagonism may directly interfere with central compensation (Chen et al, 2019), placing an even higher premium on the need for new therapeutic options. Finally, corticosteroids appear to be limited to accelerating patients' midterm recovery (Shupak, Issa, Golz, Kaminer, & Braverman, 2008), without any proven short‐ or long‐term benefit (Goudakos, Markou, Psillas, Vital, & Tsaligopoulos, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, these agents have associated side effects, with sedation being a common drawback of antihistamines, and in many cases, their efficacy in reducing vertigo is questionable (Strupp, Zwergal, Feil, Bremova, & Brandt, 2015). Recent preclinical data furthermore suggest that H 1 receptor antagonism may directly interfere with central compensation (Chen et al, 2019), placing an even higher premium on the need for new therapeutic options. Finally, corticosteroids appear to be limited to accelerating patients' midterm recovery (Shupak, Issa, Golz, Kaminer, & Braverman, 2008), without any proven short‐ or long‐term benefit (Goudakos, Markou, Psillas, Vital, & Tsaligopoulos, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of many of these agents is limited by the associated sedation, which reduces or delays central compensation, a process essential to effective long‐term recovery. Betahistine is not associated with sedation (Adrion et al, 2016; Betts, Harris, & Gadd, 1991) and has been shown to facilitate behavioural recovery both in vivo (Chen et al, 2019; Tighilet, Mourre, Trottier, & Lacour, 2007) and in patients by reducing the time to reach compensation (Parfenov et al, 2017; Redon et al, 2011). However, betahistine may exacerbate acute vertigo symptoms and this effect is likely to limit its usefulness as an acute symptomatic treatment (Kiroglu, Dagkiran, Ozdemir, Surmrlioglu, & Tarkan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Anterograde Tracing. Anterograde tracer biotinylated dextran amine (BDA) was microelectrophoresed in TMN (A -4.5, L 1.2, and H 9.6) following our previous reports (20,21,56). The immunohistochemical experiment was performed 3 wk later to determine the injection site and location of anterograde labeled histaminergic fibers.…”
Section: Methodsmentioning
confidence: 99%
“…As described in prior studies, 4,17 the asymmetric posture scoring (10 points were the maximum score) was performed to evaluate postural deficits in this study. The criteria were as follows: 10 points, spontaneous rolling; 9 points, rolling through the bubble or mild touch; 8 points, left-lateral position without leg prop; 7 points, the same lateral leg prop to the cerebral parenchyma lesion; 6 points, using the left leg prop when moving left; 5 points, prop up by both legs; 4 points, fall left randomly; 3 points, moving while tilting to the left; 2 points, inconspicuous asymmetry; and 1 point, postural asymmetry while picking them up.…”
Section: Postural Asymmetry Scoringmentioning
confidence: 99%
“…The head roll tilt scoring system was applied by measuring the angle of jaw-plane-horizontal. 17 The scoring methods applied in the present study were the same as the previously specified scoring methods. It is scored 10 when the angle is 90°or the animal body rolls to the left or lies on its left side.…”
Section: Head Roll Tilt Scoringmentioning
confidence: 99%